Workshop Hermeneutika Alkitab untuk Presbiter Jemaat GMIT Kefas Suit: Pengabdian - Anika Catharina Takene (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
The Biblical Hermeneutics Workshop conducted at GMIT Kefas Suit aimed to enhance the interpretative competencies of presbyters in reading the Bible contextually. This community service initiative employed a participatory learning approach involving interactive lectures, group discussions, and hands-on practice. A total of 30 presbyters participated in the two-day workshop, focusing on three core areas: basic hermeneutical principles, cultural context analysis, and exegesis development. Evaluation was conducted through pre- and post-tests, observation, and written reflections. Results revealed a significant improvement across all areas, with the highest gain (74%) in cultural context analysis. The workshop not only improved theoretical understanding but also fostered a transformative interpretive paradigm that is more contextual and reflective. The creation of a learning community via WhatsApp further strengthened the workshop’s sustainability. These findings suggest that context-based training grounded in real-life cases can effectively bridge the gap between seminary theories and congregational practices. In addition to producing a locally rooted hermeneutical training module, the activity inspired new congregational initiatives, including Bible study groups and contextual preaching.